Exploring the Risk Factors and Occurrence of Meningitis in Infants and Toddlers Aged 6-18 months with Initial Seizure and Fever - Taiba Abbas, Kiran Mushtaq Toor, Neelum Khan, Easha Arooj, Maham Ashraf, Naila Bai (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Meningitis is a serious neurological condition in infants and toddlers, often presenting with fever and seizures. Early diagnosis is critical, as delayed management can lead to severe complications, including neurological deficits and death. Identifying risk factors can help in early intervention and improved patient outcomes. Objective: To explore the risk factors and occurrence of meningitis in infants and toddlers aged 6-18 months presenting with initial seizures and fever. Study Design: A cross-sectional analytical study. Study Setting: The study was conducted at Department of Paediatrics Sahiwal Teaching Hospital over six months from April 2023 to September 2023. Materials and Methods: A total of 150 infants and toddlers aged 6-18 months presenting with fever and seizures were included. CSF analysis was performed to confirm meningitis. Demographic data, vaccination status, nutritional history, and clinical parameters were recorded. Risk factors were analyzed using statistical tests, with p<0.05 considered significant. Results: Meningitis was diagnosed in 38.7% of cases. Incomplete vaccination (69.0% vs. 32.6%, p<0.001), recurrent infections (55.2% vs. 30.4%, p=0.002), and malnutrition (50.0% vs. 21.7%, p<0.001) were significantly higher in meningitis patients. Mortality was 10.3% in meningitis cases compared to 1.1% in non-meningitis cases (p=0.02). Practical Implication: Early identification of risk factors such as incomplete vaccination, recurrent infections, and malnutrition can help in the timely diagnosis and management of meningitis, reducing morbidity and mortality. Conclusion: Incomplete vaccination, recurrent infections, and malnutrition were key risk factors for meningitis. Early identification and preventive measures, including vaccination, can help reduce morbidity and mortality. Keywords: Bacterial meningitis, febrile seizures, infants, lumbar puncture, neurological complications, Pakistan, risk factors, vaccination status